Programmatic research outcomes used to establish the evidence‐base of dementia caregiving support programs: An analysis of Best Programs for Caregiving - Morgan J. Minyo; Sara M. Powers; David M. Bass; Rachel M. Cannon; Katie Maslow; Zoe F. Fete; Megan K. Huth (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract INTRODUCTION A substantial number of evidence‐based dementia caregiving support programs positively impact family and friend caregivers. Researchers and service organizations have successfully translated and delivered a subset of these programs to caregivers and are included in Best Programs for Caregiving (BPC). This investigation examined the programmatic caregiver research outcomes reported in peer‐reviewed articles of BPC programs to understand how programs impact caregivers in the community and identify underrepresented outcomes. METHODS Peer‐reviewed, published research articles that (1) reported at least one dementia caregiver outcome, and (2) used a controlled trial or pre/posttest study design were abstracted from the BPC database. Across 45 evidence‐based programs in BPC, 128 articles met inclusion criteria for data coding and descriptive analysis. Research outcomes (e.g., stress, depressive symptoms), efficacy findings (e.g., beneficial, no effect), and the type of study design used (e.g., pre/posttest, treatment/control) were coded from each article. RESULTS Twelve programmatic outcomes were identified focusing on Caregiver Well‐Being and Caregiver Support. Caregiver Well‐Being outcomes were frequently assessed by BPC programs, including symptoms of depression, reported in 81 (63.3%) articles, and care‐related stress, strain, and/or burden, reported in 75 (58.6%) articles. By comparison, Caregiver Support outcomes were infrequently measured including quantity of family/friend support, reported in 17 (13.3%) articles, and quantity of community service use, reported in 13 (10.2%) articles. High percentages of beneficial findings were reported for both Caregiver Well‐Being and Caregiver Support outcomes. Articles reported beneficial findings using pre/posttest and treatment/control group designs similarly across caregiver outcomes. DISCUSSION The majority of BPC programs positively impact caregiver well‐being outcomes but limited attention is given to other person‐centered and strength‐based research outcomes including supports for caregivers, unmet needs, and positive aspects of caregiving. Additional research is needed by both established and new non‐pharmacological caregiving interventions to target and evaluate the impact of these underrepresented outcomes. Highlights Best Programs for Caregiving is an online database of dementia caregiving programs. BPC programs mainly target deficit‐focused, medical‐based, well‐being outcomes. Few BPC programs target positive aspects of caregiving and service use outcomes. More research is needed to evaluate underrepresented caregiver outcomes.